LIFE CYCLE ASSESSMENT OF CANNED CRAB PRODUCTS INDUSTRY IN PT. X MAKASSAR, SOUTH SULAWESI (Jurnal Teknologi Industri Pertanian, 2024)
Canning crab is one of Indonesia's marine products that has high economic value. Canning crab has an impact on the environment that needs to be studied. This research aims to identify the life cycle of the crab canning production process and examine the environmental impacts caused throughout the product life cycle. Canning crabs start with steaming, processing, and transporting (exporting) the crabs and pushing the Life Cycle Assessment (LCA) method with the CML-IA baseline approach, which focuses on the impact of Global Warming Potential (GWP), Acidification (AP), and Eutrophication (EP) with a functional unit of 0.454 kg per packaging. Life Cycle Assessment (LCA) uses the CML-IA baseline method to calculate the global impact of the crab canning industry in Makassar with a GWP impact of 13.04317 kg CO2 eq, an EP impact of 3.02x10-2 kg PO4 eq, and an AP impact of 6.78x10-2 kg SO2 eq. The most significant impact or hotspot is the impact of GWP, which has the most significant production process contribution from using crab can packaging. Improvement scenarios to reduce this impact are replacing can packaging with plastic, replacing LPG with natural gas, efficient water use, and efficient use of diesel. Simulation results show that this scenario significantly reduces environmental impacts, especially GWP impacts, with a reduction of 86%, followed by EP impacts of 88% and AP of 75%. Future research needs to review improvement scenarios related to economic calculations as well as testing the quality and durability of crab in plastic cup packaging.Keywords: CML-IA baseline, Canning crab, LCA, Simapro